Pengembangan Video Streaming Server Menggunakan Emby Server untuk Layanan Konten Video pada Website - Khairul Khairul; Zulfahmi Syahputra; Rian Farta Wijaya; Iwan Purnama (LKP KARYA PRIMA KURSUS, 2025)
The development of web-based multimedia content services has created a need for video distribution solutions that are efficient, controlled, and easy to manage. Many website administrators still rely on third-party platforms, resulting in limitations in terms of data control, management flexibility, and dependence on external services. This study discusses the development of a video streaming server using Emby Server as the main platform to provide video content services on a website. The methods used include system requirements analysis, the design of network architecture and streaming services, installation and configuration of Emby Server, as well as the integration of Emby with the website interface as a user access medium. Testing was carried out through functional testing (video playback, user management, access rights configuration) and performance testing (streaming stability, response time, and buffering frequency under various user load and video quality scenarios). The results show that Emby Server is capable of delivering stable video streaming services with minimal disruptions as long as network conditions remain within reasonable limits, while also facilitating administrators in managing the video library, user accounts, and streaming quality. Thus, the development of a video streaming server based on Emby Server can be considered an alternative standalone solution for websites that require video content services with greater control over data and infrastructure